2013
DOI: 10.1021/ml400213v
|View full text |Cite
|
Sign up to set email alerts
|

Discovery of Pyridyl Bis(oxy)dibenzimidamide Derivatives as Selective Matriptase Inhibitors

Abstract: Matriptase belongs to trypsin-like serine proteases involved in matrix remodeling/degradation, growth regulation, survival, motility, and cell morphogenesis. Herein, we report a structure-based approach, which led to the discovery of sulfonamide and amide derivatives of pyridyl bis(oxy)-benzamidine as potent and selective matriptase inhibitors. Co-crystal structures of selected compounds in complex with matriptase supported compound designing. Additionally, WaterMap analyses indicated the possibility of occupy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
31
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(32 citation statements)
references
References 24 publications
(45 reference statements)
1
31
0
Order By: Relevance
“…Interestingly, although matriptase is a trypsin‐like serine proteinase, it did not significantly degrade the aggrecan monomer in vitro, unlike trypsin itself. This suggests that the substrate specificity of matriptase is more restricted than that of trypsin, which is supported by previous studies , such that the observed aggrecanolysis is essentially indirect by other proteinases. This was further supported by the finding that ADAMTS4 (but not ADAMTS5 ) as well as MMPs were induced following matriptase addition to OA cartilage.…”
Section: Discussionsupporting
confidence: 84%
“…Interestingly, although matriptase is a trypsin‐like serine proteinase, it did not significantly degrade the aggrecan monomer in vitro, unlike trypsin itself. This suggests that the substrate specificity of matriptase is more restricted than that of trypsin, which is supported by previous studies , such that the observed aggrecanolysis is essentially indirect by other proteinases. This was further supported by the finding that ADAMTS4 (but not ADAMTS5 ) as well as MMPs were induced following matriptase addition to OA cartilage.…”
Section: Discussionsupporting
confidence: 84%
“…These membrane‐anchored proteases are structurally defined by a cytoplasmic N‐terminal tail, a transmembrane domain, a stem region that contains various functional domains, and a C‐terminal extracellular serine protease domain, characterized by the catalytic triad, serine, histidine and aspartate, essential for proteolytic activity . Matriptase, one of the best characterized TTSPs, is mainly expressed in epithelia, such as epidermis or thymic stoma . The proteolytic activity of matriptase is regulated by the Kunitz type hepatocyte growth factor activator inhibitors HAI‐1 and HAI‐2 .…”
Section: Methodsmentioning
confidence: 99%
“…One benzguanidine moiety is very likely to be oriented towards the deep, negatively charged S1 pocket . However, the remaining benzguanidine is either able to address the S3/S4 or the S2 pocket of matriptase . The assembly of our probe was inspired by several potent dibasic matriptase inhibitors, such as peptidic ketobenzothiazoles derived from the natural Arg‐Gln‐Ala‐Arg autoactivation sequence of matriptase, bis‐benzamidines, or sulfonylated 3‐amidinophenylalanine derivatives .…”
Section: Methodsmentioning
confidence: 99%
“…WX-UK1 was evaluated for its potential to inhibit hepsin and uPA using appropriate substrates. 51 (g) A confocal microscope image taken from human breast cancer explant. The sample was processed for Matrigel culture and kept 7 days in culture, followed by immunostaining with indicated antibodies.…”
Section: Wx-uk1 Inhibits Oncogenic Actions Of Hepsin In Mammary Epithmentioning
confidence: 99%